Coronary arteritis of Kawasaki disease unresponsive to high-dose intravenous gammaglobulin successfully treated with plasmapheresis - Mori, M; Tomono, N; Yokota, S (Nihon Rinshō Menʾeki Gakkai kaishi, 1995)
Kawasaki disease (KD) is characterized by marked activation of immune system and generalized vasculitis including coronary arteritis, and the intravenous gammaglobulin therapy is recommended as the first line of the choices. However, in some fulminant cases the coronary arteritis progresses rapidly and extensively in the early phase of the disease despite of the aggressive high-dose gammaglobulin administration. Recent observations indicated that the vasculitis begins at the endothelial cells which are activated by several inflammatory cytokines and are adhered to by cytokine-activated cytotoxic immune cells. Thus, it is important for the prevention of coronary arteritis and the resultant coronary aneurysm to reduce the inflammatory cytokines in the plasma. We reported here a 4-year-old girl with coronary arteritis which began on the 3rd day of the disease. The patient was fulfilled the revised criteria of KD at the hospital admission. As the initial intravenous gammaglobulins (400 mg/kg/day for 3 consecutive days and the subsequent 1 g/kg single intravenous infusion) revealed ineffective, which was judged by echocardiography in the persistence of brightness of the slightly widened coronary artery, and by laboratory data, we conducted therapeutic approach of plasmapheresis (replacement of plasma with 5% albumin in saline) on 8-10th days of KD. Fever was down to normal range soon after the first plasmapheresis, and after the second pheresis CRP was reduced, and finally on the 10th day echocardiography demonstrated marked improvement of inflamed coronary artery. The precise mechanism of the effective plasmapheresis is to be investigated, but it is possible that the removal of inflammatory cytokines from the plasma ceased the subsequent endothelial cell damage and coronary arteritis.(ABSTRACT TRUNCATED AT 250 WORDS)